2011
DOI: 10.3126/ajms.v1i2.3279
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Cigarette Smoking among the College Students of Kathmandu Valley

Abstract: Objective: To estimate the prevalence of smoking among the college students and to identify the factors associated with smoking. Material & Methods:This is a cross sectional study carried out on 304 college students in Kathmandu valley using purposive sampling during the months of December 2009 to January 2010.The self administrated questionnaire was adopted from Global Youth Tobacco Survey2007 (GYTS) and data were collected after the verbal consent taken. The statistical analysis was done using descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 14 publications
9
20
1
Order By: Relevance
“…Dharan (19.7%), Pokhara (47.1%), Kalaiya (25.3%) and (13.9%) among junior collegiate of western Nepal. 4,8,12,13 The prevalence of smoking among adolescencents was high in African countries i.e. Sierra Leone, Lesotho and Madagascar compared with the findings of this study.…”
Section: Discussionsupporting
confidence: 66%
“…Dharan (19.7%), Pokhara (47.1%), Kalaiya (25.3%) and (13.9%) among junior collegiate of western Nepal. 4,8,12,13 The prevalence of smoking among adolescencents was high in African countries i.e. Sierra Leone, Lesotho and Madagascar compared with the findings of this study.…”
Section: Discussionsupporting
confidence: 66%
“…Valley, revealed that males were more likely to be smokers than females due to feelings of maturity, independence and solidarity [4]. Similarly, more males than females were alcoholic in Nepal (p=0.000).…”
Section: Discussionmentioning
confidence: 95%
“…The mean age for tobacco use initiation (smoking and chewing) in our study was found to be in consistency with studies from Kathmandu, Noida, and Kerala, India where the mean ages of onset were 14.15, 12.4 and 13.2 years, respectively. [11,12,13] Early-and middle-adolescents are more vulnerable to initiation of tobacco use; hence, a target group is highlighted for early intervention to reduce the uptake of this habit.…”
Section: Methodsmentioning
confidence: 99%